(untitled) (Revista de Estudos da Linguagem, 2007)
Generative models explain the development of a child’s phonologicalsystem in terms of processes and rules, assuming that the mentalrepresentation of phonological knowledge is abstract. On the otherhand, Usage Based Phonology and Exemplar Models argue that mentalrepresentation is composed of multiple exemplars which include thephonetic detail and phonological variation. One contribution of ExemplarModel is to show that child uses fine acoustic detail to reach theadult target. The aim of this paper is to point out the contributions ofMulti-representational Models to phonological acquisitioncomprehension. We analyze the acquisition of variable patterns inBrazilian Portuguese. Results show evidence of phonetic and lexicalgradience. We argue that multi-representational models can capturethe gradual and dynamic nature of phonological acquisition.